2019
DOI: 10.35940/ijitee.j9973.0881019
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Diagnosis (BCD) Model Using Machine Learning

Abstract: In the recent years, breast cancer research has made a significant growth however there is still a scope of advancement. Breast cancer increases the statistics of mortality among women. In concern to this issue, treatment of cancer should be started at the earlier stage, to increase the chances of survival of the patient. Thus, there is a need to diagnose breast cancer at the early stage using the features from the mammograms. This paper proposes an efficient BCD model to detect breast cancer by using Support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 7 publications
(7 reference statements)
0
10
0
1
Order By: Relevance
“…[8]. Data mining and machine learning techniques are commonly used for detecting breast cancer in early stages, which can help to decrease mortality rate among breast cancer diseases [17]. These are explained briefly in the next subsections.…”
Section: Data Mining Techniques Used For Cancer Prediction 21 Data Mi...mentioning
confidence: 99%
See 3 more Smart Citations
“…[8]. Data mining and machine learning techniques are commonly used for detecting breast cancer in early stages, which can help to decrease mortality rate among breast cancer diseases [17]. These are explained briefly in the next subsections.…”
Section: Data Mining Techniques Used For Cancer Prediction 21 Data Mi...mentioning
confidence: 99%
“…The results showed that the Naïve Bayes was more accurate, with less execution time than J48. The researchers in [17] proposed an efficient Breast Cancer Diagnosis (BCD) model to detect breast cancer by using a support vector machine (SVM) with 10-fold cross validation. The complexity of the problem increases if there are many input features used to diagnose breast cancer.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Machine-learning and deep-learning methods are widely utilized for computer vision [ 11 , 12 ], image processing [ 13 ], early medical diagnosis [ 14 ], and indexing [ 15 ]. The literature review considers deep-learning and transfer-learning techniques for COVID-19 detection using several medical image modalities like CT scans, X-rays, etc.…”
Section: Literature Reviewmentioning
confidence: 99%